Well-to-wheels total energy and GHG emissions of HCNG heavy-duty vehicles in China: Case of EEV qualified EURO 5 emissions scenario. (18th March 2020) - Gupta, Pralhad; Tong, Dehui; Wang, Jingshan; Zhuge, Weilin; Yan, Changfeng; Wu, Ye; Luo, Sijie; He, Xiaoyi; Ma, Fanhua
Abstract: Energy security and climate change are critical concerns in the present era. The booming of the vehicle population has worsened the environment and has caused severe air pollution problems, especially in urban areas. The utilization of hydrogen-enriched compressed natural gas in internal combustion engines shows abundant prospects for improved performance and reduced on-road emissions of greenhouse gases and air pollutants. This study aims to provide an insight to well-to-wheels environmental implications of the 20%HCNG fuel mixture in terms of total energy use, and greenhouse gas emissions per megajoules (MJ) of thermal energy output. The well-to-tank (WTT) impacts were evaluated using GREET 1 (2017). GREET 1 is a fuel cycle modeling tool developed by 'Argonne national laboratory.' GREET® is extensively used by researchers worldwide to analytically simulate energy use and emission output of various vehicle and fuel combinations. This study uses 12 prospective pathways of gaseous hydrogen production for analysis purposes. In the tank-to-wheels (TTW) phase, the 20%HCNG@EEV reduces the brake specific energy consumption (BSEC) by approximately 5%, and also decreases GHG emissions by 14% compared with 0%HCNG@EURO3. For simplicity, EURO5 is entitled as 'EEV' and has been excluded in most of the discussion, only highlighting 'EEV, ' which abbreviates as 'Enhanced Environmentally friendly Vehicles.' For the entire well-to-wheels phase, this research work shows that all of the 20%HCNG@EEV pathways have lower total energy use and GHG emissions than 0%HCNG@EURO3 except the two pathways, such as grid electricity-to-hydrogen (without CO2 sequestration) and coal gasification-to-hydrogen (without CO2 sequestration). The WTW total energy and GHG emissions reduced by approximately 14% and 13%, respectively, with 20%HCNG@EEV based on the coke oven gas pathway compared with 0%HCNG@EURO3. It is essential to note that the use of cleaner feedstock for hydrogen, such as power-to-gas (P2G), biomass, coke oven gas (by-product), and natural gas shows tremendous prospects for realizing and practicing sustainable 'hydrogen economy' in China. Further technological advancement and reduction in total costs of HCNG utilization in powertrains will increase the number of HCNG vehicles decreasing the burden of air pollution, climate change, and energy crisis threats. Highlights: The 20% hydrogen addition to CNG reduces TTW total energy and GHG emissions. GREET1(2017) was implemented for WTT simulation to access hydrogen fuel pathways. COG-to-H2 showed potential reductions of total energy and GHGs at the WTW phase. Electrolytic hydrogen is not a sustainable choice with grid-electricity in China. At the WTW phase, 20%HCNG@EEV outperforms 0%HCNG@EURO3 with COG-to-H2 in China.